Informal employment and wages in Poland - Jacek Liwiński (Global Labor Organization (GLO), 2021)
Purpose: This paper tries to identify the wage gap between informal and formal workers and tests for the two-tier structure of the informal labour market in Poland. Design/methodology/approach: I employ the propensity score matching (PSM) technique and use data from the Polish Labour Force Survey (LFS) for the period 2009-2017 to estimate the wage gap between informal and formal workers, both at the means and along the wage distribution. I use two definitions of informal employment: a) employment without a written agreement and b) employment while officially registered as unemployed at a labour office. In order to reduce the bias resulting from the non-random selection of individuals into informal employment, I use a rich set of control variables representing several individual characteristics. Findings: After controlling for observed heterogeneity, I find that on average informal workers earn less than formal workers, both in terms of monthly earnings and hourly wage. This result is not sensitive to the definition of informal employment used and is stable over the analysed time period (2009-2017). However, the wage penalty to informal employment is substantially higher for individuals at the bottom of the wage distribution, which supports the hypothesis of the two-tier structure of the informal labour market in Poland. Originality/value: The main contribution of this study is that it identifies the two-tier structure of the informal labour market in Poland: informal workers in the first quartile of the wage distribution and those above the first quartile appear to be in two partially different segments of the labour market.
Keywords: J24; J31; J46; 330; informal workers; undeclared employment; wages; wage penalty; PSM